2018
DOI: 10.1093/gerona/gly176
|View full text |Cite
|
Sign up to set email alerts
|

Drug Burden Index and Its Association With Hip Fracture Among Older Adults: A National Population-Based Study

Abstract: In this study, increasing DBI was associated with a higher likelihood of fractures after accounting for the competing risk of mortality and adjusting for confounders. The results of this unique study are important in validating the DBI as a guide for medication management and it could help reduce the risk of hip fractures in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Anticholinergic burden, often the result of concomitant use of multiple MACs [10], has been associated with adverse effects such as cognitive and functional impairment, reduced quality of life, impaired activities of daily living [2] as well as falls [11,12] and fall-related injuries, particularly fractures [13][14][15][16]. These effects are usually associated with the person's total anticholinergic burden, rather than specific medications.…”
Section: Eligibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Anticholinergic burden, often the result of concomitant use of multiple MACs [10], has been associated with adverse effects such as cognitive and functional impairment, reduced quality of life, impaired activities of daily living [2] as well as falls [11,12] and fall-related injuries, particularly fractures [13][14][15][16]. These effects are usually associated with the person's total anticholinergic burden, rather than specific medications.…”
Section: Eligibilitymentioning
confidence: 99%
“…Of the 49 articles eligible for full-text assessment, 40 were excluded, as they did not use an anticholinergic burden scale (N = 17), did not assess fractures as an outcome (N = 10), did not report a measure of association (N = 4), or were only published as conference abstracts (N = 9). Nine studies fulfilled all eligibility criteria and were included into the systematic review, corresponding to six cohort [14][15][16][29][30][31] and three case-control studies [13,32,33].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly harmful are medications with anticholinergic and sedative properties, which are prescribed to up to a quarter of older persons (3,4). These medications have been associated with poorer cognitive functioning (5)(6)(7)(8)(9), poorer physical functioning (5,9,10), and increased risk of hip fractures (11). Anticholinergic medications exert central antagonistic effects on muscarinic receptors thereby inhibiting acetylcholine transmission within hippocampal, fusiform, inferior prefrontal cortical, and striatal areas (12)(13)(14).…”
mentioning
confidence: 99%
“…Cognitive decline and mortality have been found to be associated with an increased DBI score in some cross-sectional studies but not others 8 16. Longitudinal studies have found that an increased DBI score is independently associated with lower physical function over 5 years, poorer delayed memory performance, increased incidence of frailty and hip fracture, physician visits and mortality 14 17. These results represent 20 different studies, span multiple countries (Australia, Canada, Finland, the Netherlands, New Zealand, UK and USA) and provide a substantial argument to reduce DBI score in individuals where possible 8…”
Section: Introductionmentioning
confidence: 87%